Analisis dan Rekonstruksi Komponen Penyusun Lembar Kerja Peserta Didik Struktur dan Fungsi Jaringan Tumbuhan: (Analysis and Reconstruction of the Components of the Student Worksheet on Structure and Function of Plant Tissue) - Nadia Nadia; Bambang Supriatno; Sri Anggraeni (BIODIK, 2020)
Student worksheets are guidelines used by teachers and students in practicum activities. This study aims to analyze and reconstruct the students worksheets are less qualified and not in accordance with established standards. This research is a descriptive qualitative analysis research which aims to analyze and reconstruct student worksheets with the 1)Analysis; 2)Try; 3)Reconstruction stage. The analysis was conducted on 6 student worksheet on Plant Network Structure and Function based on the KTSP Curriculum and 2013 Curriculum using the Laboratory Activity Analysis Form instrument and the Vee Diagram scoring table. The trial was conducted at the FPMIPA Plant Structure Laboratory, Universitas Pendidikan Indonesia. Student worksheets reconstruction is based on the problems found in the conceptual, practical and knowledge construction aspects after analysis and testing. The results showed that there were problems with student worksheets in the Structure and Function of Plant Tissue from conceptual, practical and knowledge construction aspects. In the conceptual aspect, for the suitability of competence with Basic Competence and suitability of activities with the cognitive level of students, the percentage is only 16.6%. In the practical aspect 66.7% of the student worksheets analyzed the procedure incorrectly so that the phenomenon objects that appear are not relevant to the objectives / titles of student worksheets . In the aspect of knowledge construction 66.6% of student worksheets analyzed the questions can be answered without doing practicum and there are no questions about data interpretation, the emergence of a principle and analysis so that drawing conclusions is not based on facts and does not describe the title/purpose. Based on the acquisition of component scores Diagram Vee student worksheets Structure and Function of Plant Tissue has not reached an ideal score (18). The Vee Diagram component that does not appear at all is knowledge claims (score 0). Abstrak. Lembar kerja siswa merupakan pedoman yang digunakan oleh guru dan siswa dalam kegiatan praktikum. Penelitian ini bertujuan untuk menganalisis dan merekontruksi lembar kerja siswa yang kurang berkualitas dan tidak sesuai dengan standar yang telah ditetapkan. Penelitian ini merupakan penelitian analisis deskriptif kualitatif yang bertujuan untuk menganalisis dan merekontruksi lembar kerja siswa dengan metode ANCOR (Analisis-Coba-Rekontruksi). Analisis dilakukan pada 6 LKS Struktur dan Fungsi Jaringan Tumbuhan berdasarkan Kurikulum KTSP dan Kurikulum 2013 menggunakan instrumen Form Analisis Kegiatan Laboratorium dan tabel penskoran Diagram Vee. Uji coba dilakukan di Laboratorium Struktur Tumbuhan FPMIPA Universitas Pendidikan Indonesia. Rekontruksi LKS dilakukan berdasarkan permasalahan yang ditemukan pada aspek konseptual, praktikal dan kontruksi pengetahuan setelah melakukan analisis dan ujicoba. Hasil penelitian menunjukkan bahwa terdapat permasalahan pada LKS Struktur dan Fungsi Jaringan Tumbuhan dari aspek konseptual, praktikal dan kontruksi pengetahuan. Pada aspek konseptual, untuk kesesuaian kompetensi dengan Kompetensi Dasar dan kesesuaian kegiatan dengan tingkat kognitif siswa, persentasenya hanya 16,6%. Pada aspek praktikal 66,7% dari LKS yang dianalisis prosedurnya tidak tepat sehingga objek fenomena yang muncul tidak relevan dengan tujuan/judul LKS. Pada aspek kontruksi pengetahuan 66,6% dari LKS yang dianalisis pertanyaannya dapat dijawab tanpa melakukan praktikum dan tidak ada pertanyaan mengenai interpretasi data, kemunculan suatu prinsip dan analisis sehingga penarikan kesimpulan tidak berdasarkan fakta dan tidak menggambarkan judul/tujuan. Berdasarkan perolehan skor komponen Diagram Vee LKS Struktur dan Fungsi Jaringan Tumbuhan belum mencapai skor ideal (18). Komponen Diagram Vee yang tidak muncul sama sekali adalah klaim pengetahuan (skor 0).